Head-Up; An interdisciplinary, participatory and co-design process informing the development of a novel head and neck support for people living with progressive neck muscle weakness. (3rd October 2015) - Reed, Heath; Langley, Joe; Stanton, Andy; Heron, Nicola; Clarke, Zoe; Judge, Simon; McCarthy, Avril; Squire, Gill; Quinn, Ann; Wells, Oliver; Tindale, Wendy; Baxter, Susan; et al.
Abstract: This paper presents the Head-Up project, that aims to provide innovative head support to help improve posture, relieve pain and aid communication for people living with progressive neck muscle weakness. The initial focus is motor neurone disease. The case study illustrates collaborative, interdisciplinary research and new product development underpinned by participatory design. The study was initiated by a 2-day stakeholder workshop followed by early proof-of-concept modelling and patient need evidence building. The work subsequently led to a successful NIHR i4i application funding a 24-month iterative design process, patenting, CE marking and clinical evaluation. The evaluation has informed amendments to the proposed design refered to here as the Sheffield Support Snood (SSS). The outcome positively demonstrates use and performance improvements over current neck orthoses and the process of multidisciplinary and user engagement has created a sense of ownership by MND participants, who have since acted as advocates for the product.